Yield and Quality of Tomato Juice as Affected by Ripening Agents - Haque, MM; Aziz, MG; Mortuza, MG; Rahman, MA (Journal of Environmental Science and Natural Resources, 2019)
The effects of ethephon on acceleration of ripening as well as differentiation of quality and juice yield of tomato fruit were evaluated. Three groups of ethophon namely Ripen-15 (50% ethephon), Lpen-25 (48% ethephon) and Fast-25 (40% ethephon) along with control solution were applied on mature and uniform shaped tomato at three concentrations (10 ppm, 100 ppm, 1000 ppm). Physical and chemical attributes such as color, firmness, total weight loss, total soluble solids (TSS), vitamin C content, pulp smoothness and juice yield were studied from 3rd to 13th day of application of ethephon. The fastest yield of tomato juice was obtained from 100 ppm as compared to the slowest at 1000 ppm. The highest and lowest juice yield were found by application of Lpen-25 and Fast-25 respectively at 1000 ppm Thus, we concluded that ethephon application on tomato at an appropriate level may accelerate the ripening of tomato fruit and increase the yield of tomato juice. J. Environ. Sci. & Natural Resources, 11(1-2): 183-189 2018